2019
DOI: 10.3390/jcm8050739
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Elastography of Liver in Light Chain Amyloidosis

Abstract: In this paper, we present our preliminary findings regarding magnetic resonance elastography (MRE) on the livers of 10 patients with systemic amyloidosis. Mean liver stiffness measurements (LSM) and spleen stiffness measurements (SSM) were obtained. Magnetic resonance imaging (MRI) images were analyzed for the distribution pattern of amyloid deposition. Pearson correlation analysis was performed in order to study the correlation between LSM, SSM, liver span, liver volume, spleen span, spleen volume, serum alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
4
0
2
Order By: Relevance
“…A study enrolling 10 patients with systemic amyloidosis found Pearson correlation coefficient between serum ALP and NT-proBNP was 0.13 ( P value not significant). 35 Therefore, our preliminary conclusions on the independent predictive effect of ALP may be meaningful, and future studies should add BNP/NT-proBNP or troponin in the univariable and multivariable analysis to further explore its predictive value for all-cause mortality.…”
Section: Discussionmentioning
confidence: 86%
“…A study enrolling 10 patients with systemic amyloidosis found Pearson correlation coefficient between serum ALP and NT-proBNP was 0.13 ( P value not significant). 35 Therefore, our preliminary conclusions on the independent predictive effect of ALP may be meaningful, and future studies should add BNP/NT-proBNP or troponin in the univariable and multivariable analysis to further explore its predictive value for all-cause mortality.…”
Section: Discussionmentioning
confidence: 86%
“…Die Elastografie ergibt eine erhöhte Lebersteifigkeit. Diese kann heterogen, diffus oder eher fokal sein [21].…”
Section: Amyloidoseunclassified
“…Hierro hepático elevado puede ocurrir debido a enfermedad renal en el contexto de amiloidosis renal lo cual es evaluado con MR, con imágenes ponderadas en T2, como una hipointensidad difusa. El amiloide depositado en hígado puede ser evaluado por elastografia por MR, con un incremento de la rigidez, por lo menos dos veces mas de lo normal (58,59).…”
Section: Amiloidosis Hepáticaunclassified